Higher vitamin D levels in HIV‐infected out‐patients on treatment with boosted protease inhibitor monotherapy1. Issue 9 (5th June 2013) - Cervero, M; Agud, JL; Torres, R; García‐Lacalle, C; Alcázar, V; Jusdado, JJ; Moreno, S
Abstract : Objectives: We investigated the vitamin D status of patients receiving frequently used types of combination antiretroviral therapy (cART), including boosted protease inhibitor (PI) monotherapy. Methods: For this cross‐sectional study, out of 450 HIV‐infected patients followed in the Hospital Severo Ochoa (Madrid, Spain), we selected 352 patients for whom vitamin D levels had been measured (January 2009 to December 2010). We collected the following data: demographics, cART duration, main cART regimen, viral load (VL), CD4 cell count, and concentrations of 25(OH)‐vitamin D [25(OH)‐D], parathyroid hormone (PTH), albumin and calcium. Vitamin D status cut‐off points were: (1) deficiency (vitDd): 25(OH)‐D < 20 ng/mL; (2) insufficiency (vitDi): 25(OH)‐D from 20 to 29.99 ng/mL; and (3) optimal (vitDo): 25(OH)‐D ≥ 30 ng/mL. Results: The percentages of patients with vitDd, vitDi and vitDo were 44, 27.6 and 28.5%, respectively. Twenty‐nine out of 30 (96.7%) Black patients had vitDd or vitDi, vs. 71.6% in the global sample ( P  < 0.001). Former injecting drug users (IDUs) had a higher prevalence of vitDo ( P  < 0.001) than patients in other transmission categories. Among patients with vitDd, vitDi and vitDo, the proportions of patients with a VL ≤ 50 HIV‐1 RNA copies/mL were 77.4, 68 and 91%, respectively ( P  < 0.0001). Of the cART regimens, only boosted PI monotherapy was associated with significant differences in vitamin D levels ( P  = 0.039). Multivariate logistic regression analysis showed an increased risk of vitDi or vitDd associated with the following variables: Black vs.  Caucasian ethnicity [odds ratio (OR) 10.6; 95% confidence interval (CI) 1.2–94; P  = 0.033]; heterosexual (OR 2.37; 95% CI 1.13–4.93; P  = 0.022) or men who have sex with men (MSM) (OR 3.25; 95% CI 1.25–8.50; P  = 0.016) transmission category vs. former IDU; and VL > 50 copies/mL (OR 2.56; 95% CI 1.10–7.25; P  = 0.040). A lower risk of vitamin D insufficiency or deficiency was found in patients on boosted PI monotherapy vs. no treatment (OR 0.08; 95% CI 0.01–0.6; P  = 0.018). Conclusions: Our data show an increased risk of vitamin D deficiency or insufficiency in patients with detectable VL and a Black ethnic background. Among cART regimens, boosted PI monotherapy was associated with a lower risk of vitamin D deficiency or insufficiency. The more favourable vitamin D status in former IDUs was probably attributable to a higher frequency of outdoor jobs in this group of patients.